Application of the Hermite Series Kernel Density Estimator in Identifying the Confrontational Hazards of Maritime Piracy on Nigeria’s Economic Growth - Ejakpovi, Simeon Uyovwieyovwe; Uveruveh, Francis Okeoghene; Siloko, Israel Uzuazor; Ishiekwene, Cyril Chukwuka (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
Maritime piracy prevalence is a global phenomenon that anchors mostly on the illegal lifting of crude oil in the Nigeria waters. It is an illegal act of depredation, committed for isolated ends by the crews of private sea vessels which has degraded the economic growth of the Nigeria economy. This research aims to examine the hazardous effects of piracy in the Niger Delta region (NDR) using novel nonparametric density estimation methods on the nation’s economy. The maritime piracy data showed that there are five-hundred and ninety-four (594) menace incidence in the NDR that negatively affected the annual gross domestic product (GDP) and annual incomes in million Dollars in the Nigeria economy within the period of 2002-2024. The positive economic growth index was recorded in 2002 and negative growth rates recorded in 2016 and 2020 by both model estimators. The kernel density estimator (KDE) and Hermite Series kernel density estimator (HSeKDE) Mathematical model estimators’ visualizations of both economic growth rates and maritime piracy incidence hinged on the model estimators smoothing parameter and the kernel functions. In contrast to the KDE model visualizations, the HSeKDE estimator through the Gaussian kernel and others captured the multiple undulating patterns of piracy incidence persistence and rippled economic growth rates. This was possible with the aid of the smoothing parameter and kernel functions applied in the model estimator to ascertain the influx in the Nigeria economy. Also, the asymptotic mean integrated squared error (AMISE) is the error criterion whose least value of 0.00000125586 and 0.0000460329 were obtained for maritime piracy incidence, while that of economic growth rate is 0.0000010743 and 0.000039378 using the Epanechnikov and Gaussian kernels. These AMISE values obtained from the sea theft incidence affirmed its occurrence in the Nigeria seas while that of the economic growth rates affirmed the indemnities of the incessant sea theft in the Nigeria waters have adversely affected the country’s economic growth rate stability. Therefore, we recommend that fund appropriation should be allocated to foster the training of personnel and purchase of modern robotic security equipments to halt all forms of sea theft in the Niger Delta region (NDR).